2016
DOI: 10.1016/j.neuropharm.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific localization of NMDA receptors on oligodendrocytes dictates axon function recovery after ischemia

Abstract: Oligodendrocytes and axons are the main targets of an ischemic white matter injury and the resultant loss of axon function underlies the clinical disability in patients who survive a stroke. The cellular mechanisms of ischemic injury change as a function of age in concordance with age-mediated structural changes in white matter. Shorter periods of injury cause rapid and robust loss of axon function together with widespread oligodendrocyte death. While blockade of NMDA receptors fails to benefit axon function, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…GS in OLs could also play a role in the regulation of myelination, since the overexpression of GS in Schwann cells was shown to enhance myelin production (Saitoh and Araki, 2010). Besides, it may explain the failure of NMDA antagonists in stroke clinical trials, as the blockage of OLs NMDA receptors worsens axons functional recovery (Baltan, 2016). Here, we detected the expression of glutamate receptors predominantly in NG2 cells.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…GS in OLs could also play a role in the regulation of myelination, since the overexpression of GS in Schwann cells was shown to enhance myelin production (Saitoh and Araki, 2010). Besides, it may explain the failure of NMDA antagonists in stroke clinical trials, as the blockage of OLs NMDA receptors worsens axons functional recovery (Baltan, 2016). Here, we detected the expression of glutamate receptors predominantly in NG2 cells.…”
Section: Discussionmentioning
confidence: 61%
“…Such dramatic difference between gray and white matter OLs points to a region-specific glutamate regulation of axon-myelin interactions. Besides, it may explain the failure of NMDA antagonists in stroke clinical trials, as the blockage of OLs NMDA receptors worsens axons functional recovery (Baltan, 2016). Another interesting observation was the different expression of Grm3/5.…”
Section: Discussionmentioning
confidence: 97%
“…It is likely that aging, as a result of lower calreticulin and calnexin levels, impairs SER Ca 2ϩ homeostasis (Coe and Michalak, 2009) and impedes aging axon function recovery following OGD (Baltan et al, 2008;Baltan, 2015). This is an appealing suggestion particularly because removal or attenuation of Ca 2ϩ influx confers complete protection to axon function in young MONs after OGD (60 min) becomes ineffective or injurious in MONs from 12-month-old mice, even after short durations of OGD (30 -45 min; Baltan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although these results suggest that individual mitochondria become elongated with age, we further evaluated axonal ultrastructural changes using 3-D EM to determine a structure-function basis for age-related alterations in molecular architecture and response to ischemia (Baltan, 2012(Baltan, , 2015. Since 12 months of age marks the beginning of increased sensitivity to ischemic injury (Baltan et al, 2008;, our 3-D EM studies primarily compared MONs at 1 and 12 months (Fig.…”
Section: Aging Increases Nodal Length and Internodal Distancesmentioning
confidence: 99%
“…Emerging data suggests that the activation of OLG NMDA receptors is not likely contributing to WM damage, and blocking NMDA receptors provided no protection in ischemic WM injury [18,19]. What is more, individual evidence even confirmed that blocking NMDA receptors may actually worsen the functional outcome of aging in WM in response to ischemia [20]. Besides those mentioned above, the views concerning the role of non-NMDA receptors such as the AMPA/kainate glutamate receptor in ischemic OLG damage are also conflicting [21].…”
Section: Other Mechanisms Of Ischemic Olgs Damagementioning
confidence: 99%